Infusion pump - ALLWORTH, PETER CLINTON; FEINGOLD, VLADIMIR (1988)
A portable infusion pump assembly utilizing continuous drive propulsion means (8) to effect automatic and incremental displacement of a plunger (5) within a disposable syringe (3) so as to deliver accurately repeatable volumes of fluid from the syringe (3) over a predetermined period of time. Intermittent drive of the continuous drive propulsion means (8) is effected. Comparison of desired delivery rate with actual delivery rate is made by use of angular displacement signals received from a shaft encoder (10) attached to the shaft of the continuous propulsion means (8). This method of control also allows indirect measurement of fluid pressure in the syringe (3) without the need for a pressure sensor to be located in direct contact with the fluid being delivered.